Capacity Building Of Personnel Resources In Order To Improve Employee Performance (Studies in Regional Employment Board of Malang) - Ilmi Fadhim Azumi (Jurnal Administrasi Publik, 2015)
Abstract: Capacity Building of Personnel Resources in Order to Improve Employee Performance (Studies in Regional Employment Board of Malang). The change of Law Number 8 of 1974 to Law Number 43 of 1991 about The Principles of Employee Affair, the most fundamental changes of employee management is more oriented in Human Resources (HR) Apparatus professionalism. In this case, based on LAN, human resources of the State Apparatus is basically matters relating to the position, duties, rights, powers and responsibilities of HR Apparatus as state officials (2003, p.247). One way that can be done in the development of civil servants is through education and training. Regional Employment Board of Malang Government, a government agency has the task in personnel using a variety of employee development programs that might be expected to improve the capability, performance and quality of its employees. The cause of the decline in the performance of civil servants in Malang Government is the culture and society are still not conducive to creating an environment that makes one valid discipline because they are afraid of the boss. Employee Performance of Malang Government is basically good, but not optimal. It can be seen from the efficiency and effectiveness work and employee discipline. Â  Keywords: capacity building, training, human resources apparatus Abstrak: Pengembangan Kapasitas Sumber Daya Aparatur Dalam Rangka Meningkatkan Kinerja Pegawai (Studi Pada Badan Kepegawaian Daerah Kota Malang). Perubahan Undang-Undang Nomor 8 tahun 1974 menjadi Undang-Undang Nomor 43 tahun 1991 tentang Pokok-Pokok Kepegawaian, perubahannya yang paling pokok adalah tentang manajemen kepegawaian yang lebih berorientasi pada profesionalisme Sumber Daya Manusia (SDM) Aparatur. Dalam hal ini, berdasarkan LAN, SDM Aparatur Negara pada hakekatnya merupakan hal-hal yang berkenaan dengan kedudukan, tugas, hak, wewenang dan tanggungjawab SDM Aparatur selaku penyelenggara negara (2003, h.247). Salah satu cara yang dapat dilakukan dalam upaya pengembangan pegawai negeri sipil adalah melalui pendidikan dan pelatihan ( diklat). Badan Kepegawaian Daerah Pemerintah Kota Malang, merupakan instansi pemerintah mempunyai tugas dalam bidang kepegawaian menggunakan berbagai program pengembangan pegawai yang nantinya diharapkan dapat meningkatkan kemampuan, kinerja serta kualitas para pegawainya. Penyebab menurunnya kinerja pegawai negeri di Pemerintahan Kota Malang adalah kultur dan masyarakat kita yang masih belum kondusif untuk menciptakan lingkungan yang membuat seseorang berlaku disiplin karena mereka merasa takut pada atasan. Kinerja Pegawai Pemerintah Kota Malang pada dasarnya sudah baik, tetapi belum optimal. Hal ini dapat dilihat dari efisiensi dan efektivitas kerja dan disiplin pegawai. Â  Kata kunci: pembangunan kapasitas, pendidikan dan pelatihan, sumber daya aparatur